The effect of using a mixture of banana stems and tofu dregs at different levels on nutrient consumption of landrace grower crossbred pigs - Wea, Redempta; Koten, Bernadete B.; Mbeong, Yustus S.N.; Suban, Ignasius B.; Anugrah, Dedet S.G.; Malawati, Ima; Canadianti, Monica; Paga, Agustinus (Fakultas Peternakan Universitas Papua, 2026)
Banana stems and tofu dregs are agricultural and industrial waste that can be used as pig feed. However, the high crude fiber content requires fermentation technology to be used as pig feed. The purpose of this study was to examine the nutrient consumption of Landrace crossbred pigs consuming fermented banana stems tofu dregs (FBSTD) at different levels. This study was conducted in the pig pen of Rizky's farm from April to June 2025. The study used a Randomized Block Design (RBD) with 4 treatments and 3 replications. The research treatments were R0: Ration without FBSTD, R1: Ration containing 10% FBSTD, R2: Ration containing 20% FBSTD, and R3: Ration containing 30% FBSTD. The research data were analyzed using analysis of variance and Duncan's further test. The research variables were nutrient consumption (dry matter, crude fiber, crude fat, and ash). The results showed that increasing the percentage of FBSTD use (0%, 10%, 20%, and 30%) significantly affected (P<0.05) dry matter (DM) consumption and significantly affected (P<0.01) crude fiber (CFi) consumption, crude fat (CFa) consumption, and ash consumption. This also increased DM (1710.84±124,54 to 914.57±29,93 gram/head/day), CFa (132.55±9,65 to 216.19±3,38 g/h/d), and ash (212.15±15,44 to 251.54±9,78g/h/d) consumption and decreased CFi ((376.42±27,40 to 287.61±4,50g/h/d) consumption when using 20% FBSTD. In conclusion, the use of FBSTD increased DM, CFa , and ash consumption and decreased CFi consumption at the 20% level. It is recommended that FBSTD be used at 20% in grower pig rations.